A Systematic Literature Review of Shockley’s Subjective Career Success Inventory (SCSI) and its Application to Career Satisfaction Development in Indonesia - Casmini, Casmini; Apriari, Shinta Ath Thariq (Jurnal Psikologi, 2025)
The Subjective Career Success Inventory (SCSI) can be applied to and understood by the Indonesian work culture, which has unique social norms, collectivism, and a hierarchical structure. This study aims to analyze the suitability and relevance of SCSI based on empirical findings on career satisfaction development, synthesize the factors influencing subjective career success in the Indonesian context, and identify the research gaps arising from the question of how Shockley’s Subjective Career Success Inventory (SCSI) can explain and support the understanding of career satisfaction development within Indonesia’s socio-cultural and organizational landscape. The review process adheres to methodological standards and PRISMA guidelines to ensure transparency, involving thematic analysis that examines the eight dimensions of the SCSI while considering the local cultural context to develop a culturally valid and relevant measurement of subjective career success in Indonesia. The literature review results indicate that career success in the SCSI dimensions encompasses eight main aspects influenced by various individual, social, and cultural factors. In Indonesia, the interpretation and realization of career success are greatly influenced by social norms, collectivist values, and the balance between self-authenticity and harmony in the workplace, resulting in a unique dynamic and challenges in the concept of career success shaped by cultural context. These findings contribute significantly to enriching the understanding of subjective career success by highlighting how the Indonesian cultural context shapes the dynamics of authenticity, social influence, and the meaning of work that impact the achievement of holistic career success.